Encounters and conversations: an office café space as a “magnet space” - Tai Satoh; Tomonori Sano (Japan Architectural Review, 2020)
Abstract A study was conducted on the activities of office workers at a café space with a lounge in a free‐address office to investigate communication at a “magnet space.” The major results were as follows: (i) The encounter probability between two office workers at the magnet space could be estimated by a formula based on Little's law, which considers the frequency of use as well as the mean and standard deviation of the stay time. Analyzing more data for the estimated formula of the encounter rate, which is suggested in this study, can confirm more thoroughly the actual situation of an encounter and conversation in the magnet space of the office. (ii) Installing a lounge‐like workspace adjacent to the café space increased the encounter probability between workers at the café space.